Evaluation of the synergistic potential of vancomycin combined with other antimicrobial agents against methicillin-resistant Staphylococcus aureus and coagulase-negative Staphylococcus spp strains - Lívia Viganor da Silva; Manuela Tedesco Araújo; Kátia Regina Netto dos Santos; Ana Paula Ferreira Nunes (Memorias do Instituto Oswaldo Cruz, 2011)
Methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative Staphylococcus spp (CNS) are the most common pathogens that cause serious long term infections in patients. Despite the existence of new antimicrobial agents, such as linezolid, vancomycin (VAN) remains the standard therapy for the treatment of infections caused by these multidrug-resistant strains. However, the use of VAN has been associated with a high frequency of therapeutic failures in some clinical scenarios, mainly with decreasing concentration of VAN. This work aims to evaluate the synergic potential of VAN plus sulfamethoxazole/trimethoprim (SXT), VAN plus rifampin (RIF) and VAN plus imipenem (IPM) in sub-minimum inhibitory concentrations against 22 clinical strains of MRSA and CNS. The checkerboard method showed synergism of VAN/RIF and VAN/SXT against two and three of the 22 strains, respectively. The combination of VAN with IPM showed synergistic effects against 21 out of 22 strains by the E-test method. Four strains were analyzed by the time-kill curve method and synergistic activity was observed with VAN/SXT, VAN/RIF and especially VAN/IPM in sub-inhibitory concentrations. It would be interesting to determine if synergy occurs in vivo. Evidence of in vivo synergy could lead to a reduction of the standard VAN dosage or treatment time.